A new reproductive mode in anurans: Natural history of Bokermannohyla astartea (Anura: Hylidae) with the description of its tadpole and vocal repertoire - Malagoli, Leo Ramos [UNESP]; Pezzuti, Tiago Leite; Bang, Davi Lee; Faivovich, Julian; Lyra, Mariana Lucio [UNESP]; Ribeiro Giovanelli, Joao Gabriel [UNESP]; Anchietta Garcia, Paulo Christiano de; Sawaya, Ricardo Jannini; Baptista Haddad, Celio Fernando [UNESP] (Public Library Science, 2021)
Anurans have the greatest diversity of reproductive modes among tetrapod vertebrates, with at least 41 being currently recognized. We describe a new reproductive mode for anurans, as exhibited by the Paranapiacaba Treefrog, Bokermannohyla astartea, an endemic and poorly known species of the Brazilian Atlantic Forest belonging to the B. circumdata group. We also describe other aspects of its reproductive biology, that are relevant to understanding the new reproductive mode, such as courtship behavior, spawning, and tadpoles. Additionally, we redescribe its advertisement call and extend its vocal repertoire by describing three additional call types: courtship, amplectant, and presumed territorial. The new reproductive mode exhibited by B. astartea consists of: (1) deposition of aquatic eggs in leaf-tanks of terrestrial or epiphytic bromeliads located on or over the banks of temporary or permanent streams; (2) exotrophic tadpoles remain in the leaf-tanks during initial stages of development (until Gosner stage 26), after which they presumably jump or are transported to streams after heavy rains that flood their bromeliad tanks; and (3) tadpole development completes in streams. The tadpoles of B. astartea are similar to those of other species of the B. circumdata group, although with differences in the spiracle, eyes, and oral disc. The vocal repertoire of B. astartea exhibits previously unreported acoustic complexity for the genus. Bokermannohyla astartea is the only bromeligenous species known to date among the 187 known species within the tribe Cophomantini. We further discuss evolutionary hypotheses for the origin of this novel reproductive mode.